2016
DOI: 10.1111/cid.12414
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Medications and the Survival Rate of Osseointegrated Dental Implants: A Cohort Study

Abstract: Our findings suggest that treatment with antihypertensive drugs may be associated with an increased survival rate of osseointegrated implants. To our knowledge, this could be the first study showing that the systemic use of a medication could be associated with higher survival rate of dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 56 publications
(111 reference statements)
6
67
0
7
Order By: Relevance
“…Five calcium channel blockers, the only antihypertensive medications abstracted, were used among the 548 patients with implants in the antihypertensive medication category, and no increased risk of implant failure was identified. This finding was in contrast to a published study on medication users (n = 142) and nonusers (n = 586) that reported a reduced risk of implant failure in patients receiving hypertension medications . In that study, which analyzed implant‐level failure, Wu et al found a higher implant survival rate among the users of antihypertensive medications than nonusers (HR, 0.12; 95% CI, 0.03‐0.49).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Five calcium channel blockers, the only antihypertensive medications abstracted, were used among the 548 patients with implants in the antihypertensive medication category, and no increased risk of implant failure was identified. This finding was in contrast to a published study on medication users (n = 142) and nonusers (n = 586) that reported a reduced risk of implant failure in patients receiving hypertension medications . In that study, which analyzed implant‐level failure, Wu et al found a higher implant survival rate among the users of antihypertensive medications than nonusers (HR, 0.12; 95% CI, 0.03‐0.49).…”
Section: Discussionmentioning
confidence: 60%
“…This finding was in contrast to a published study on medication users (n = 142) and nonusers (n = 586) that reported a reduced risk of implant failure in patients receiving hypertension medications. 21 In that study, which analyzed implant-level failure, Wu et al found a higher implant survival rate among the users of antihypertensive medications than nonusers (HR, 0.12; 95% CI, 0.03-0.49).…”
Section: Antihypertensive Medicationsmentioning
confidence: 97%
“…Abuohashish, Ahmed, Sabry, Khattab, and Al‐Rejaie () reported that some antihypertensive drugs (renin–angiotensin system medicines) improve bone metabolism and the strength of bone. Additionally, Wu et al () reported that the implant survival rate is higher in patients taking antihypertensive drugs than in healthy patients. The reason for these differences from our findings is that the systemic diseases of the subjects participating in our study were relatively well controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Wu et al (2016) reported that the implant survival rate is higher in patients taking antihypertensive drugs than in healthy patients. The reason for these differences from our findings is that the systemic diseases of the subjects participating in our study were relatively well controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Antihypertensive drugs have a positive effect in implant dentistry in a clinical setting, however, the causes are unclear. 26,27 Considering the systemic anabolic effects of these drugs, 19,22,24 beneficial effects on alveolar bone are to be expected. It can be proposed that antihypertensive drugs help to maintain the alveolar bone microstructure.…”
Section: Introductionmentioning
confidence: 99%